International trade and collective bargaining outcomes: Evidence from German employer-employee data - Gabriel Felbermayr; Andreas Hauptmann; Hans-Jörg Schmerer (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
In theoretical trade models with variable markups and collective wage bargaining, export exposure may reduce the exporter wage premium. We test this prediction using linked German employer-employee data from 1996 to 2007. To separate the rent-sharing mechanism from assortative matching, we exploit individual worker information to construct profitability measures that are free of skill composition. We find that rent-sharing is less pronounced in more export intensive firms or in more open industries. The exporter wage premium is highest for low productivity firms. In line with theory, these findings are unique to the subsample of plants covered by collective bargaining. – – In theoretischen Handelsmodellen mit variablen Aufschlägen auf die Grenzkosten, kann eine Ausweitung der Exporte den Exportlohnaufschlag verringern. Wir überprüfen diese Aussage anhand von verknüpften Arbeitnehmer-Arbeitgeber Daten für den Zeitraum 1996-2007. Um den Rent-Sharing Mechanismus vom Assortative-Matching Argument zu trennen, nutzen wir individuelle Arbeitnehmerinformationen um ein Profitabilitätsmaß zu generieren, welches frei von der Qualifikationsstruktur ist. Wir finden, dass Rent-Sharing in exportintensiven Betrieben oder offeneren Branchen weniger ausgeprägt ist. Der Exportlohnaufschlag ist in Betrieben mit niedrigerer Produktivität am stärksten. Entsprechend der Theorie betrifft dieses Ergebnis Betriebe, die unter Tarifvereinbarungen fallen.
Keywords: F16; J51; E24; J3; 330; trade; unions; collective bargaining; employer-employee data; Internationale Wirtschaft; Exportwirtschaft; Lohnbildung; Tarifpolitik; Schätzung; Deutschland